Analysis of the influence of mechanical element discontinuities on unbalancing - Gladson Willian Pereira Rodrigues; Paulo Cezar Büchner; Alexandre Martins Reis; Charles Luís da Silva; Natália Rie Horikawa; Estéfani de Vargas Ventorim (The Journal of Engineering and Exact Sciences)
The study of rotor unbalancing is essential for safety and reliability in the design of machinery and other mechanical structures with rotating parts. By understanding the dynamic behavior and effects of unbalanced components, engineers can address this issue and establish a maintenance program to safeguard mechanical systems from excessive vibrations and prevent catastrophic failures, primarily due to fatigue. Balancing in one and two planes is the most common procedure to correct unbalanced masses in rotating parts. In this work, the aim is to advance the understanding of the effects of mass distribution in irregular-section parts and develop a tool to calculate and improve balancing. In certain situations, there are local limitations to corrections, such as adding correction mass due to irregularities and machine element constraints. To validate the proposed solution, a sample of a crankshaft and a camshaft actuation mechanism was used, where unbalancing is a common issue due to the inherent geometric discontinuities in these types of components. The achieved result demonstrated the validity of the application, allowing the balancing of the samples within the levels recommended by the standard.